Pengaruh Kesiapan Teknologi, Sumber Daya Manusia, Kerumitan, Keamanan Dan Kerahasiaan Terhadap Minat Dalam Menggunakan E-Filing - Oka Mahendra Putra, I Putu (E-Jurnal Akuntansi; Vol 29 No 1 (2019), 2019)
This study aims to determine the Effect of Technology Readiness, Human Resources, Complexity, Security and Confidentiality on Individual Taxpayers in using e-filing (Case Study of Individual Taxpayers in South Badung KPP). This research was conducted at the KPP Pratama Selatan Badung. The population number that will be examined in this research in 2017 is 115,324 taxpayers, while the number of samples taken is 100 taxpayers, with the nonprobability sampling method and purposive sampling technique. Data collection is done by distributing questionnaires. The method of data analysis uses multiple linear regression analysis. Based on the results of the study show that the readiness of technology, human resources, security and confidentiality has a positive effect on the interest of individual taxpayers in using e-filing, while the complexity has a negative effect on the interest of individual taxpayers in using e-filing. Keywords : Technology; HR; Complexity; Security And Confidentiality; E-Filing.